Pengaruh Pemberian Quadriceps Strengthening Exercise pada Osteoarthritis Lutut : Studi Kasus - Putri Intan Sari; Taufik Eko Susilo (Jurnal Kesehatan dan Fisioterapi, 2022)
Introduction: Osteoarthritis is a joint disorder characterized by progressive degeneration of articular cartilage resulting in loss of joint space. Structural abnormalities of all tissues in the joints including subchondral cartilage, synovium, capsule, and ligaments. In patients with osteoarthritis often found muscle weakness in the quadriceps. Strengthening exercise is an exercise that is given to strengthen muscles. Objective: to determine the effectiveness of giving strengthening exercise in patients with osteoarthritis. Methods: Single subject research conducted on patients with osteoarthritis 63 years. Subjects were given exercises using the strengthening isometric exercise method for 4 weeks which were carried out 2x/week and motor evaluation was carried out at the end of the study. Result : Evaluation was conducted using Manual Muscle Testing and Jette Scale measurement instruments. At the baseline, muscle strength is a value of 4 which means that it can fight minimal resistance, after 8 treatment sessions there is an increase in muscle strength to a value of 5 that can fight maximum resistance. Functional measurement using the Jette scale at baseline had a total score of 18 (mild disability), then after being given treatment for 4 weeks the total score became 15 (normal). Conclusion: there is an increase in muscle strength and an increase in functional ability in osteoarthritis patients after being given strengthening isometric exercise for 4 weeks.Keywords: Osteoarthritis, muscle weakness, strengthening exercise.